History-dependent molecular dynamics in nanoporous host matrices - Kärger, Jörg; Valiullin, Rustem (Diffusion Fundamentals, 2008)
Ensembles of molecules confined to pore spaces with diameters of the order of a couple of molecular diameters reveal features which may notably deviate from their behaviour both in the bulk phase and under dominating host-guest interaction. We are going to demonstrate that under identical external conditions (temperature, pressure), different ensemble "histories" may give rise to dramatic differences in the states of these ensembles. PFG NMR diffusion measurements are introduced as a most sensitive tool for probing these differences.